Shaping the Spirituality of Communion in Church Communities - Polak, Mieczysław Kazimierz (Verbum Vitae, 2020)
The activity of the Church results from its identity, and one constitutive element of this identity is the dimension of community. It is expressed, above all, by shaping the spirituality of communion in church communities. This spirituality has its foundations in the communion character of the presbyter's pastoral ministry and refers to the gospel commandment of love. It is shaped by Christian prayer centered on the Eucharist. The spirituality of communion built upon such foundations should permeate church community structures, which are made up, first and foremost, by parishes. On their own, parishes are not able to pass on the experience of church communion. Only by being infused with the spirituality of communion can they become spaces for experiencing the community dimension of the Church's life.